Avaliação da resistência de genótipos de milho doce à lagarta do cartucho, Spodoptera frugiperda (J.E.Smith) (Lepidoptera: Noctuidae) - Mulati, Náyra Cristiane de Souza Crubelati (2014)
The use of resistant genotypes is important for integrated pest control and has been deserves attention in plant breeding programs. The cropping of sweet corn (Zea mays L. subsp. Saccharata) is quite similar to that of common corn, especially in relation to the occurrence of pests. In both cultures, the fall armyworm, Spodoptera frugiperda ( JE Smith , 1797 ) (Lepidoptera : Noctuidae ), is a pest that causes major economic losses. However, information about the impact of pests in sweet corn are scarce, so that the study of possible genotypes for resistance is required. This work aimed to evaluate nine cultivars of sweet corn and two resistant controls of regular corn for resistance to S. frugiperda. The experimental design was completely randomized with 27 replicates per genotype/treatment. The experiments were carried out in environmental temperature, photoperiod and humidity controlled (24 ± 1 ° C, 12 hours and 70 ± 10 %, respectively) in laboratory. Data were subjected to analysis of variance and subsequently the means were compared by the Scott-Knott test (p < 0.1) test. It was found that the BR -400 ,Tuc Dulce Blanco, MG 161, Doce Flor da Serra, Doce Cubano, Tropical Plus , BRS 1030 and Zapalote Chico genotypes are more favorable to the development of S. frugiperda, while Milho Doce 1 , MG 162 , Tuc Blanco Dulce and Doce Opaco genotypes are less favorable for insect development